Contact Activation in the Extrinsic Blood Clotting System - Altman, R; Hemker, H. C (Thrombosis and Haemostasis, 1967)
After contact activation, factor XII can convert factor VII into its active form. Factor XI enhances this action but appears not to be a compulsatory part of the system. The short circuit of the intrinsic system constituted by this pathway may be important in triggering the intrinsic coagulation system.